Anti- plasmid effect of some plant extracts against multidrug resistant Enterococci. - Issa, Mohsen Ayoub (Journal of medical and pharmaceutical sciences, 2018)
Multiple drug resistance (MDR) is one of the most important global health challenges requiring constant research. Most of the genetic determinants responsible for this resistance are located on plasmids. The present research was carried out to investigate the anti- plasmid activity of alcoholic extracts of Sumach (Rhus Coriaria) and Sage (Salvia officinalis) against antibiotics resistant Enterococci. Antibiotics sensitivity test results showed that all these bacteria isolates possess different types of multidrug resistance had reached up to nine out of fourteen antibiotics، All isolates showed absolute resistance (100%) to the Amikacin and Naldixic acid. Results of anti- plasmid activity investigation of Sumach and Sage alcoholic extracts against Enterococci selected isolates، was demonstrated the plasmid curing with a concentration of (2000 μg / cm3) ، by the loss of antibiotic resistance characteristic toward (Amikacin، Ampicillin، acid Naldixic and Tetracycline) and molecular loss of two plasmids (Size 4000 bp & 3500 bp)، which demonstrating the presence of resistance genes of above- mentioned antibiotics on the cured plasmids. Therefore، this result open the way to possibility of using these two plants after additional studies to treatment the problem of drugs resistance in Enterococci and other pathogenic bacteria.
Keywords: plasmid; plant extract; enterococci; MDR